The Comparative Effects of Input Enhancement and Input Flooding on the Learning of Apology and Request Speech Acts among EFL Learners: The Case of Computer-mediated vs. Traditional Methods - Bakhshi Jahromi, Iman; Ahmadi Shirazi, Masoumeh; Khomijani Farahani, Ali Akbar (Assessment and Practice in Educational Sciences, 2024)
This study examines how input enhancement and input flooding, delivered via traditional vs. computer-mediated instruction, affect EFL learners’ mastery of the speech acts apology and request. One hundred twenty intermediate learners (both male and female) were selected by convenience sampling. Using a quasi-experimental design, four experimental groups each received one of the treatment combination. Data analysis involved one-way ANOVA, and independent-samples t-tests. Results show that the computer-mediated input flooding group achieved the highest mean score in pragmatic knowledge (≈ 17.67), whereas the traditional input enhancement group performed lowest (≈ 12.90). The other two groups (computer-mediated enhancement; traditional flooding) were between these extremes, with no statistically significant difference between them. All groups showed improvement in performing apology and request speech acts, with greater gains in the computer-mediated conditions. There was no significant gender difference. Flooding, especially when delivered through computer mediation, is particularly effective for enhancing pragmatic competence.